Terrorist Recruitment and the International System - Kassab, Hanna Samir, 1984- (Lanham : Lexington Books, 2020)
This book describes the resilience of terrorist groups by studying recruitment and its impact on the individual, the state, and the international system.
Keywords: Terrorist organizations; Legitimacy of governments; Terrorism; Legitimacy of governments; Terrorism; Terrorist organizations